The hostage. - Behan,Brendan; Gevanthor, Norman; Behan, Brendan; Coe, Richard L. (Richard Livingstone), 1914-1995; Arena Stage (Organization : Washington, D.C.); Richard L. Coe Theater Programs Collection (Library of Congress) (london., 1972)
Arena Stage, Zelda Fichandler, producing director, Thomas C. Fichandler, executive director presents in the Kreeger "The Hostage," by Brendan Behan, directed by Norman Gevanthor, set designed by John Conklin, costumes designed by Marjorie Slaiman, lighting designed by Vance Sorrells, musical preparation by Alan Rafel, dances by Virginia Freeman, technical director Henry R. Gorfein, associate director Alan Schneider, associate producer Hugh Lester.
Arena Stage, October 27, 1972.
Title devised by Library staff.
Cast: Leslie Cass, Robert Prosky, Max Wright, Carl Thoma, Dorothea Hammond, Judith Long, Vladimir Chernozemsky, Richard Bauer, Stanley Anderson, Beulah Garrick, Dianne Wiest, Howard Witt, Gary Bayer, Augustine Dunn, Jay McMillan.
LC copy has notations by Coe. Accompanied by typewritten memo with notes about the Kreeger Theater.
In: Richard L. Coe Theater Programs Collection (Library of Congress).
Keywords: Theater programs -- Washington (D.C.); Theater programs -- 1972.